The Sydney Harbour Bridge: from modernity to post-modernity in Australian fiction - Genoni, Paul (Association for the Study of Australian Literature, 2012)
This paper examines the Sydney Harbour Bridge as it has been represented in a series of Australian novels that focus on the period of its construction. Contemporary interest in the Bridge is contrasted with the period of its construction when, despite its very obvious appeal to visual artists, the Bridge was all but ignored by writers of fiction. It is argued that these recent novels look back at the construction of the Bridge through a post-modern lens, at a time when the Bridge has transcended its roots in functional interwar-modernity and been reinvented as a centrepiece of Australia’s most visible and theatrical urban space.